2002
DOI: 10.1677/joe.0.1740447
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroepiandrosterone treatment attenuates oestrogen-induced pituitary hyperplasia

Abstract: The physiological importance of and therapeutic interest in dehydroepiandrosterone (DHEA) has been predominantly in relation to its action as an inhibitor of the promotion and progression of several kinds of tumours, including those of breast, prostate, lung, colon, liver and skin tissues. The aim of the present study was to determine the role of DHEA in diethylstilboestrol (DES)-induced pituitary hyperplasia. Female Sprague-Dawley rats were divided into four treatment groups: DES (implanted s.c. with a 20 mg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 49 publications
2
9
0
Order By: Relevance
“…On the other hand, DHEA pretreatment reduced the inhibitory action of somatostatin on GH, and not on prolactin, secretion. These results could be related to the DHEAinduced reversal of the inhibitory effect of ether stress on GH secretion, which we have previously described (Suárez et al 2002). From our results, it can be inferred that DHEA may release GH in vivo by reducing somatotrope responsiveness to somatostatin, as well as by enhancing somatotrope sensitivity to GHRH.…”
supporting
confidence: 80%
See 3 more Smart Citations
“…On the other hand, DHEA pretreatment reduced the inhibitory action of somatostatin on GH, and not on prolactin, secretion. These results could be related to the DHEAinduced reversal of the inhibitory effect of ether stress on GH secretion, which we have previously described (Suárez et al 2002). From our results, it can be inferred that DHEA may release GH in vivo by reducing somatotrope responsiveness to somatostatin, as well as by enhancing somatotrope sensitivity to GHRH.…”
supporting
confidence: 80%
“…In a previous work we showed that in pituitary hyperplasia induced by estrogen in female rats, DHEA had several endocrine and metabolic effects, which depended mainly on the endocrine environment (Suárez et al 2002). We found that DHEA enhanced serum prolactin in rats in diestrus, though it partially reversed estrogen-induced hyperprolactinemia.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…This could be due to changes in the proliferation/apoptosis balance or to a hyperplasia or hypertrophy. In this sense, chronic administration of estrogen or long-acting estrogenic hormone preparations is known to produce this effect [Díaz-Torga et al, 1998;Suárez et al, 2002]. Although several studies have described gonadotrophin abnormalities in PCOS, the mechanism underlying the altered LH/FSH ratio has remained unclear.…”
Section: Discussionmentioning
confidence: 99%